Upaya Meningkatkan Kepercayaan Diri Siswa dalam Bertanya di Kelas melalui Layanan Bimbingan Kelompok dengan Menggunakan Teknik Modeling di SMP Negeri 17 Kota Jambi - Yosi Fatkuliza; Nelyahardi Gutji; Fellicia Ayu Sekonda (Departement of Mathematics Education, 2023)
Confidence is a person's belief in the ability possessed to present well in front of others. While asking is one of the elements in learning, and indicates an interaction between individuals.This research is limited to the problem of increasing student confidence in asking questions in class by using group guidance services and using modeling techniques given to class VIII A students at SMP Negeri 17 Kota Jambi. The modeling technique is one of the TT techniques by presenting a pilot to the client about how to do something or how something happens. By seeing, observing or observing other people who can bring a client's understanding and can change a behavior.The type of this research was service follow-up research (PTL). The subjects in this study were 6 students in class VIII A, SMP Negeri 17 Jambi City with the initials, SPR, AZA, WUL, KNA, RRJ and AAL. This research was conducted in 3 cycles, each cycle consisting of planning, implementing, evaluating, reflecting. To see the results of the cycle he did by collecting observation data, interviews, questionnaires.The results showed that modeling techniques can increase students' confidence in asking questions in class. Of the three cycles carried out, the third cycle had the best results, namely the confidence in asking questions in class reached 92% with the accuracy of implementing the techniques carried out by researchers based on the results of questionnaires that had been carried out by researchers for each cycle that had been carried out. Obtain the results of the first cycle with an overall percentage of 12%, while the second cycle with a percentage of 69%. The results of this study are expected to help Guidance and Counseling Teachers to develop knowledge in increasing students' confidence in asking questions in class.